Utility of Ultrasound-Guided Fine Needle Aspiration Cytology in Various Pathological Lesions: A Clinico-Pathological Audit - N, Kumarguru B; C, Deepika; M J, Nirmala; A S, Ramaswamy; R, Ramesh Kumar (Annals of Pathology and Laboratory Medicine, 2024)
Background: Fine Needle Aspiration Cytology (FNAC) is a simple investigation for the pre-operative diagnosis of palpable lesions of superficial organs. Ultrasound-guided FNAC provides an avenue for the characterization of masses by both the radiologist and the pathologist, facilitating better patient care. Aim: To evaluate the utility of ultrasound-guided fine needle aspiration cytology in various pathological lesions through a clinicopathological audit process. Materials and Methods: This was a retrospective observational study conducted at a tertiary care referral institute from July 2020 to June 2021. All cases of USG-guided FNAC were included in the study. Repeat aspirations, cytological-clinical diagnostic concordance, and cytological-ultrasonography diagnostic concordance were analyzed. All statistical analyses were performed using Microsoft Excel 2007. Results: Fifty-two cases were analyzed. The most common site of aspiration was the thyroid gland (50%). The most common clinical diagnosis was a solitary nodule of the thyroid (21.15%). The most common ultrasonography diagnosis was a colloid nodule of the thyroid (26.93%). The most common cytological diagnosis was a colloid nodule of the thyroid (28.85%). Repeat aspirations were performed in 31 cases (59.62%). Haemorrhagic material (46.15%) was the most common reason for repeat aspiration. Cytology-clinical diagnostic concordance was 83.33% based on partial concordance criteria. Cytology-ultrasonography diagnostic concordance was 95.65% based on partial concordance criteria. Conclusion: Ultrasonography serves to specifically target lesions and enables accurate cytological diagnosis. Clinicians and radiologists should strive to provide more specific diagnoses for the benefit of patients. Such clinicopathological audits help identify and rectify gaps in patient care.